The Bird Study Book - Pearson, T. Gilbert (Thomas Gilbert), 1873-1943 (Salt Lake City, UT : Project Gutenberg, 2007)
"The Bird Study Book" by T. Gilbert Pearson is a scientific guide on ornithology written in the early 20th century. This work serves as an introduction for beginners interested in studying the habits and activities of wild birds, while emphasizing the relationship between birds and their environment, particularly in the context of human impact. It aims to cultivate a greater understanding and appreciation for avian life through careful observation and natural study. The opening of the book lays the groundwork for bird study, highlighting the connection between spring and bird activity, which is particularly vibrant during mating and nesting periods. Pearson encourages readers to familiarize themselves with common birds in their regions and offers practical advice for observing these creatures without intruding on their natural behaviors. He emphasizes the importance of patience and caution when seeking out nests and details various methods to enhance the bird study experience, such as using field glasses and maintaining notes on observations. With his hope to inspire a love for the subject in budding ornithologists, Pearson outlines foundational concepts that will be expanded upon in subsequent chapters. (This is an automatically generated summary.)
Release date is 2007-04-08
E-text prepared by Al Haines
Keywords: Birds; Birds -- Conservation